Detection of ethanol in Brazilian gasoline station attendants. Issue 7 (24th February 2015) - Borille, Bruna Tassi; Fiorentin, Taís Regina; Coppe, Bruna Claudia; Comiran, Eloisa; Bemvenuti Jacques, Ana Laura; Vieira Sousa, Tanara Rosângela; Pasa, Graciela Gema; Pechansky, Flavio; Maris de Jezus Castro, Stela; Limberger, Renata Pereira
Abstract : In Brazil, gasoline station attendants are regularly exposed to the ethanol contained in fuel, as well as the one used as the gasoline additive. Abstract : In Brazil, gasoline station attendants are regularly exposed to the ethanol contained in fuel, as well as the one used as the gasoline additive. This study aimed to assess the potential exposure of these workers to fuels, using breathalyzers and oral fluid (OF) analysis by headspace gas chromatography/mass spectrometry (HS-GC/MS). Attendants of 26 gasoline stations were invited to respond to a questionnaire covering the main features of the study population and the profile of drinking and driving behavior, followed by a breath test and OF collection with a Quantisal™ device. All OF samples were analyzed by HS-GC/MS. Ethanol was found in 100% of the OF samples whereas 72.83% had concentrations above the quantification limit of the method (0.00125 g dL −1 ). Regarding the breath tests, only one exhaled air sample (0.62%) showed a positive result (0.03 mg L −1 ). The positive results in OF samples and negative results in exhaled air may be explained by the higher sensitivity of OF analysis by HS-GC/MS, when compared to the breathalyzer.